Gereja yang Bertumbuh menurut Rick Warren dan Implikasinya di Gereja Toraja Jemaat Ebenhaezer Palopo - Reyka Dhesta Vira; Wandrio Salewa (Sekolah Tinggi Alkitab Jember, 2023)
This article aims to describe the concept of a growing church according to Rick Warren and its relevance to the Toraja Church of the Ebenhaezer Congregation in Palopo. A growing church according to Rick Warren is living loving one another and doing the preaching of the Gospel. The ideas built by Rick Warren are very relevant and good to be used as a measure for the church to experience growth. Based on the author's observations, within the scope of the Ebenhaezer Palopo congregation there is an inharmonious relationship as a fellowship which can have a negative impact in the midst of the ministry and the congregation. The research method used is a qualitative method using a library approach, observation and descriptive analysis. A growing church is a church that is moved by the Holy Spirit so that it produces fruit according to what has been ordained by God. So that there will be an increase in church members, expansion of ministry, mutual love, fellowship, unity, obedience to the Word of God, extensive evangelism and construction of church facilities. So that the church's goals can be achieved, namely to spread the good news about Jesus Christ and to love God and others. Tulisan ini hendak menguraikan gambaran tentang konsep gereja yang bertumbuh menurut Rick Warren dan relevansinya bagi gereja Toraja jemaat Ebenhaezer Palopo. Gereja yang bertumbuh menurut Rick Warren yaitu hidup saling mengasihi dan melakukan pemberitaan Injil. Gagasan yang dibangun oleh Rick Warren sangat relevan dan baik untuk dijadikan ukuran bagi gereja untuk semakin mengalami pertumbuhan. Berdasarkan observasi penulis, dalam lingkup jemaat Ebenhaezer Palopo terjadi relasi yang tidak harmonis sebagai satu persekutuan yang dapat membawa dampak negatif di tengah-tengah pelayanan dan jemaat. Metode penelitian yang digunakan adalah metode kualitatif dengan menggunakan pendekatan kepustakaan, pengamatan dan deskriptif analisis. Gereja yang bertumbuh adalah gereja yang digerakkan oleh Roh Kudus sehingga menghasilkan buah sesuai dengan yang telah ditetapkan oleh Allah. Agar terjadi pertambahan anggota jemaat, meluasnya pelayanan, saling mengasihi, adanya persekutuan, persatuan, taat firman Allah, pekabaran Injil yang luas dan pembangunan fasilitas gereja. Sehingga tujuan gereja dapat tercapai yaitu mengabarkan kabar sukacita tentang Yesus Kristus dan mengasihi Tuhan serta sesamanya.